Phytochemical screening and determination of minerals and heavy metals in the flowers of Nyctanthes arbor-tristis L (Bangladesh Journal of Scientific and Industrial Research, 2019)
Dried powder of the flowers of Nyctanthes arbor-tristis L. was analyzed for phytochemical screening, proximate compositions, mineral constituents and heavy metals analysis. The phytochemical screening indicated the presence of carbohydrates, flavonoids, glycosides, cardiac glycosides, reducing sugar, saponins, steroids, tannins and terpenoids. Alkaloids, anthraquinones and phlobatannins were absent. The proximate compositions was found to be high in moisture content (92.27 ± 0.09 %), the ash content was found to be (0.53 ± 0.02 %) while the protein content was 0.97 ± 0.05 % by fresh weight basis. The air dried flowers sample revealed highest in oxygen content (50.16 %) and lowest in sulfur content (0.10%). A total of six anions were analyzed. The sample was found rich in fluoride (94.87 ± 2.501 mg/Kg) and sulfate (165.24 ± 5.14 mg/Kg) content. A total of fifteen metals were analyzed. Heavy metals such as Pb, Cd, Hg, Cr and As were found in trace amounts, which were within the acceptable limits according to WHO and FAOBangladesh J. Sci. Ind. Res.54(4), 321-328, 2019